Numerative und Numerativkonstruktionen im Deutschen und im Chinesischen. Eine kontrastiv-typologische Untersuchung - Chen, Aizheng (Reihe Germanistische Linguistik, 1996)
This is a study in contrastive typology with reference to German and Chinese nouns and noun constructions. The comparison proceeds from the differences displayed by the two languages in connection with numeralization (combination of noun and numeral). In the framework of the apprehension dimension of the UNITYP approach, an attempt is first made to characterize the two languages as two different types, i.e. with numeral classification on the one hand as opposed to agreement in gender and number on the other. On this basis the numeratives and numerative constructions of the two languages are then described and compared from various perspectives. The numeratives are listed in relatively exhaustive catalogues and compared and contrasted in terms of word explanations and areas of use. The study is of interest for research into language typology and universals, as well as for practical language acquisition.